An Index of the Yields of Junk Bonds, 1910–1955. (24th November 2017) - Basile, Peter; Kang, Sung Won; Landon-Lane, John; Rockoff, Hugh
Abstract : We present a new monthly index of the yields on junk bonds (high risk, high yield bonds) for the period 1910–1955. This index supplements the indexes of government bond yields, and Aaa and Baa corporate bond yields economic historians have relied on previously to describe the long-term risk spectrum. First, we describe our sources and methods. Then we show that our junk bond index contains information that is not in the closest alternative, and suggest some ways that the junk bond index could be used to enrich our understanding of the turbulent middle years of the twentieth century.